Missionary ventures of Ghanaian Pentecostals in Europe An exploration of "Reverse Mission" within the Church of Pentecost in Belgium - Oppong-Konadu, Kwame (Missionalia, 2023)
In missiology, scholars have often used conceptual models to represent specific trends emerging from Christian missions. However, these models occasionally run the risk of oversimplification. "Reverse mission" is one such model. It concerns a supposition that Southern Christians have come to Europe to "re-Christianise" those who have fallen from the faith they initially brought to them. Through a rigorous qualitative methodology, this article investigates the reverse mission model within the Ghanaian-led Church of Pentecost (CoP) in Belgium, a product of previous European mission work in Ghana. The paper argues that while scholars sometimes easily describe the foreign mission praxis of Southern churches in the North as "reverse mission," upon closer examination, the intention of "reverse mission" seems absent from the missionary activities of some of these churches. The CoP in Belgium gives credence to this argument as empirical data from congregants indicate that the church is deeply involved in "internal mission" and only marginally active in "reverse mission."